Non-Cash Transaction Implementation In Local Government - Vira Maulina; Irwan Taufiq Ritonga (Universitas Muhammadiyah Malang, 2021)
This research is aimed to analyze the implementation of Non-Cash Transactions (NCT) in Local Government A and Local Government B by using four dimensions of public policy implementation model, namely communication, resources, disposition, and bureaucracy structure. Moreover, this research also identifies the factors which cause the low implementation of NCT in Local Government A when compared to Local Government B. This research uses the qualitative approach with multiple case studies. Researchers hope to see the comparison of NCT implementation in two different local governments to get more comprehensive picture of the effectiveness of NCT implementation in those local governments. Data collection was carried out through in-depth interviews using a semi-structured interview type and reviews on documents related to the implementation of NCT. The research data were analyzed using a thematic analysis and cross case analysis. The result of this study shows that the implementation of NCT in Local Government A was worse when compared to Local Government B. The factors that led to the low implementation of NCT in Local Government A were the lack NCT socialization to the community, limited facilities and infrastructure, weak commitment of the leader, and the absence of reward and punishment mechanisms.